Framework for improving quality and comparability of non-financial reporting system - Peršić, Milena; Bakija, Katarina; Vlašić, Dubravka (Copernican Journal of Finance & Accounting, 2015)
This research was aimed at evaluating the methodological framework to be applied in strategic as well as in responsibility accounting, as a prerequisite for ensuring the relevant information, necessary for preparing and evaluating sustainable development strategies, using Directive 2014/95/EU framework. In order to assess the current situation in the Republic of Croatia, a survey on the sample of 64 big Croatian companies in different industries in the year 2013 was conducted. The sample of selected companies was chosen on the basis of membership in the Croatian Business Council for Sustainable Development (HR BCSD) and of the companies that follow the principles of sustainable development in their business and declare themselves as environmentally and socially responsible. Research results will be confirmed through comparison with previous findings conducted in the year 2007, but also compared with the relevant information collected from 71 companies of eight EU countries. The goal is to assess whether the achieved level of strategic and sustainable accounting tools in the Croatian companies are sufficient to provide relevant information for non-financial reporting for external and internal users in the process of long and short term decision making. Recognized gaps will be the starting points for defining the opportunities and areas in the process of harmonization between internal and external sustainability reporting system. The goal is in recognizing starting points, opportunities and areas, which are important for internal and external sustainability reporting, taking into, account the provisions of the globally accepted standards and the new EU Directive.